Volunteer Recruitment Information System with Interview Scheduling Using Web-Based Greedy Algorithm - Muhammad Rezeki Fasya; Muhamad Alda (Journal of Information Systems and Technology Research, 2025)
The rapid advancement of digital technology has significantly influenced the management of non-profit and educational organizations, including volunteer recruitment processes. Gerakan Sumut Mengajar (GSM), a volunteer-based educational movement in North Sumatra, still relies on manual tools such as Google Forms and WhatsApp for participant registration, file verification, and interview scheduling. This manual approach creates inefficiencies, scheduling conflicts, and delays that reduce the professionalism of the recruitment process. The main research problem addressed in this study is the lack of an integrated system capable of handling the multi-stage recruitment process, especially in automating interview scheduling, which is prone to human error and administrative overload. The objective of this study is to design and implement a web-based volunteer recruitment information system equipped with an automatic interview scheduling mechanism using the Greedy Algorithm. The system was developed using the Waterfall software development model, implemented with PHP Native and MySQL. The Greedy Algorithm, particularly the Activity Selection Problem approach, was applied to optimize interview scheduling by allocating available slots efficiently according to the number of interviewers and candidates. The results demonstrate that the system successfully automates registration, document verification, and interview scheduling while minimizing scheduling conflicts. Compared with manual methods, the proposed solution reduces administrative workload, enhances efficiency, and provides a more professional recruitment experience. This study contributes to the development of intelligent scheduling systems in volunteer-based organizations and highlights the applicability of heuristic algorithms in solving real-world scheduling problems.